The Mechanism and Treatment of Cognitive Dysfunction in Diabetes: A Review - Hou, Yangbo; Chen, Zhen; Cheng, Jiwei; Li, Guoyi; Yin, Lu; Gao, Jie (Experimental and Clinical Endocrinology & Diabetes, 2025)
Diabetes mellitus (DM) is one of the fastest growing diseases in terms of global incidence and seriously affects cognitive function. The incidence rate of cognitive dysfunction is up to 13% in diabetes patients aged 65–74 years and reaches 24% in those aged >75 years. The mechanisms and treatments of cognitive dysfunction associated with diabetes mellitus are complicated and varied. Previous studies suggest that hyperglycemia mainly contributes to cognitive dysfunction through mechanisms involving inflammation, autophagy, the microbial-gut-brain axis, brain-derived neurotrophic factors, and insulin resistance. Antidiabetic drugs such as metformin, liraglutide, and empagliflozin and other drugs such as fingolimod and melatonin can alleviate diabetes-induced cognitive dysfunction. Self-management, intermittent fasting, and repetitive transverse magnetic stimulation can also ameliorate cognitive impairment. In this review, we discuss the mechanisms linking diabetes mellitus with cognitive dysfunction and propose a potential treatment for cognitive decline associated with diabetes mellitus.
Keywords: cognitive dysfunction; diabetes; mechanism; treatment